Carbon-doped boron nitride nanosheet as a promising metal-free catalyst for NO reduction: DFT mechanistic study - Tanabat Mudchimo (2018)
© 2018 Elsevier B.V. Currently, metal-based catalysts are commonly used to convert highly toxic gases like NO molecules into less toxic gases, such as N2O molecules through the process of reduction reaction that has a low activation energy (Ea) and high efficiency. Due to the high cost, environmental hazards and limited supply of metal-based catalysts, development of metal-free catalysts that are low cost and environmentally friendly has increased. For this research, NO reduction mechanism using the carbon-doped boron nitride nanosheets (CBNs) as a metal-free catalyst was investigated by density functional theory (DFT). For the NO reduction mechanism, the dimer mechanism pathway was investigated using the following equation: 2NO → N2O + Oad. In addition, the catalytic activity of carbon atom substitution onto BNs for NO reduction was studied. The results showed that the trans-(NO)2structure of CNBNs (D5) is a potentially crucial intermediate with thermodynamically and kinetically favorable, in which the calculated rate-determining step along the most energetically favorable pathway is 0.62 eV. Hence, our results presented here suggest that CNBNs can be a highly active metal-free material in NO removal, which will reduce NO into environmentally friendly gases.